Catasauqua, Pa. - American Oleograph Co.; Fowler & Bailey.; C.H. Vogt (Firm) (1873)
Includes index to points-of-interest.; Relief shown by shading and landform drawings.; Available also through the Library of Congress Web site as a raster image.; LC copy imperfect: Brittle, darkened at edges, torn at edges, taped on verso.; Oriented with north toward the upper left.; Aerial view of the borough of Catasauqua (Pa.).